Towards Integrated E-Government Services: Key Contributing Factors from a Whole-of-Government Perspective - Othman, Mohamed Hairul; Razali, Rozilawati; Nasrudin, Mohammad Faidzul (PT Mattawang Mediatama Solution, 2025)
Despite various initiatives introduced to ensure electronic government (e-government) services remain relevant, there are still unresolved issues in its implementation that bring negative perceptions towards the government. One common issue is the existence of duplicated as well as unintegrated services between agencies that mislead citizens and cause bureaucratic red tape. This issue could be resolved by establishing integrated e-government services, which nevertheless require strong collaboration from multiple agencies. One strategy to strengthen cross-agency collaboration is through the Whole-of-Government (WoG) approach. However, studies concerning the WoG approach that specifically focus on collaboration strategies to address service integration issues in e-government are scarce. This study therefore aimed to identify the WoG factors that are important for strengthening cross-agency collaboration, as the effort for establishing integrated e-government services. It adopted the qualitative method approach, consisting of theoretical and empirical studies. The theoretical study was conducted through literature reviews, whereas the empirical study involved semi-structured interviews with relevant informants from public and private sectors as well as statutory body. Both theoretical and empirical data were analysed using thematic analysis. The identified WoG factors were categorised into people, process and technology aspects, which can act as a guideline towards integrated e-government services through cross-agency collaboration.